Pengaruh Penerapan Metode Talaqqi dan Takrir Terhadap Kualitas Hafalan Al-Qur’an Santri - Tajul Fadli; Rumbang Sirojudin; Supardi Supardi; Wasehudin Wasehudin (Publikasi Indonesia, 2023)
This study aims to determine the effect of applying the talaqqi and takrir methods to the quality of memorizing the Koran. The research hypotheses include: 1) There is an effect of the application of the talaqqi method on the quality of memorizing the Koran. 2) There is an effect of the application of the takrir method on the quality of memorizing the Koran. 3) There is a mutual influence between the application of the talaqqi and takrir methods to the quality of students' memorization of the Koran at Al-Ihsan Kadomas Islamic Boarding School, Pandeglang. The method used in this study is a quantitative method with correlational and regression analysis. The reachable population is the students of the Al-Ihsan Kadomas Islamic Boarding School, Pandeglang in 2022 who take part in the Al-Qur'an takhassus program as many as 149 students. The sample size is 30 students, with the sampling technique used is random sampling. Variable data on the application of the talaqqi and takrir methods were obtained through a questionnaire, while data on the quality of memorizing the Qur'an were obtained through tests. Test the validity of the instrument using product moment calculations. The instrument reliability test uses Cronbach's Alpha calculations. The results showed that: first, there was a positive and significant effect of the application of the talaqqi method on the quality of students' Al-Qur'an memorization, the contribution of the application of the talaqqi method to the quality of students' memorization of the Qur'an was 47.7%; secondly, there is a positive and significant effect of the application of the takrir method on the quality of students' Al-Qur'an memorization, the contribution of the application of the takrir method to the quality of students' memorization of the Qur'an is 61.3%; third, there is a positive and significant effect of the application of the talaqqi and takrir methods on the quality of students' Al-Qur'an memorization, the contribution of the application of talaqqi and takrir methods to the quality of students' memorization of the Qur'an is 98%; Improving the quality of students' memorization of the Qur'an can be done through the application of the talaqqi and takrir methods.